The national SotePeda 24/7 project develops future professional competencies for the digital health and social care sector in Finland - Värri, Alpo Olavi; Kinnunen, Ulla-Mari; Pöyry-Lassila, Päivi; Ahonen, Outi (Finnish Journal of eHealth and eWelfare, 2019)
The SotePeda 24/7 project, financed by the Finnish Ministry of Education and Culture, aims at increasing competencies in developing digital services in the health and social care sector, and to create digital pedagogical solutions to support multidisciplinary learning. The national project, encompassing practically all the relevant universities of applied sciences educating health and social care workers, and two universities in Finland, defines the required eHealth skills and develops educational material, pedagogy and learning environments for the participating organizations. The project covers also eHealth service design skills, management skills, co-developing and the ethical aspects in the new digitally supported health and social care environments.